Analisis Spasial Tata Guna Lahan terhadap Tingkat Kerusakan Jalan di Kecamatan Padang Utara - Rizki, Rizki; Rahmayana, Lintang (REKSABUMI, 2025)
Padang Utara District in Padang City exhibits diverse land use characteristics, which in turn influence the condition of road infrastructure within the area. This study aims to identify the spatial correlation between land use patterns and the level of road damage in Padang Utara District using a map overlay technique. A mixed-methods approach was employed, combining qualitative analysis through direct observation and visual map analysis, with quantitative analysis through traffic volume measurements and the proportion of road damage across different land use zones. Primary data were obtained from field observations of physical road conditions and traffic counts in various land use areas. Secondary data were sourced from the 2024 Padang City Statistics Agency (BPS) and the Padang City Spatial Plan (RTRW) 2010–2030. The findings reveal that commercial and service areas account for the highest level of road damage, comprising up to 81% of the total recorded damage points, largely influenced by high traffic volumes, heavy road loads, and intense activity in these zones. In contrast, office areas contributed only 9% of the total road damage, while public service facilities accounted for merely 2%, despite relatively high traffic volumes. This is attributed to the predominance of light vehicles and different patterns of road use. This study is expected to provide insights into the spatial relationship between land use characteristics and road infrastructure conditions, thereby supporting more effective road maintenance planning.